PENGARUH LINGKUNGAN KERJA DAN HUBUNGAN INTERPERSONAL TERHADAP MOTIVASI KERJA GURU GUGUS EMPAT KECAMATAN SENAPELAN - RATNA DEWI; ISJONI ISJONI; HADRIANA HADRIANA (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
The aim of this research is to know about the influence between variables (1)work environment toward teacher work motivation in elementary schools of Senapelan Subdisctrict Pekanbaru, (2) interpersonal relationships toward teacher work motivation in elemantaryschools of Senapelan Sub disctrict Pekanbaru, (3) work environment and interpersonalrelationships together toward teacher motivation in elementary schools of Senapelan Sub disctrictPekanbaru. This research carried out by share out the instruments for 126 teachers in elementaryschools of Senapelan Sub disctrict Pekanbaru by using proportionate random sampling technique.The instrument used to collect the data of all variables using the questionnaire. Validity wastested using Pearson product moment formula. Instrument reliability coefficient was calculatedusing Cronbach alpha formula. The results showed a positive relationship between: (1) Thereis a positive influence between work environment toward teacher work motivation in elementaryschools of Senapelan Sub disctrict Pekanbaru with a correlation coefficient rx1. y = 0,295 andthe regression equation 79,795 + 0,233 X1. (2) There is a positive influence between interpersonalcorrelation toward teacher work motivation in elemantary schools of Senapelan Sub disctrictPekanbaru with correlation coefficients rx2. y = 0,493 and the regression v = 68,48 + 0,329 X2.(3) There is a positive influence between work environment and interpersonal correlation towardteacher work motivation in elementary schools of Senapelan Sub disctrict Pekanbaru with Rx1x2.y multiple correlation coefficient = 0,531 and the regression equation v = 56,91 + 0,159 X1 +0,301 X2. The results of this study are expected to be useful for the improvement andenhancement of teae herwork behaviour in elemantary schools of Senapelan Sub disctrictPekanbaru by increasing work environment and interpersonal correlation.